Faculty experiences and motivations in design thinking teaching and learning - McLaughlin, Jacqueline E.; Lake, Danielle; Chen, Elizabeth; Guo, Wen; Knock, McKenna; Knotek, Steve (Frontiers in Education, 2023)
Introduction: Design thinking (DT) is a creative, iterative approach to generating solutions that are desirable, feasible, and viable. Given its role in fostering creativity and innovation, a growing number of higher education instructors are teaching DT. Exploring how and what instructors know about DT and why they might teach it could provide critical insight into the ways in which DT is operationalized in higher education teaching and learning. Materials and Methods: A convergent parallel mixed methods design was used for data collected from online surveys administered to faculty teaching DT. The survey included items about DT practices, outcomes from DT, demographic characteristics, and course characteristics. Five open-text survey items queried participants about their definition of DT, why they teach DT, and what additional outcomes they observed. Descriptive statistics were used to analyze quantitative items and thematic analysis was used to analyze qualitative items. Results: Participants (n=49) represented various academic ranks, disciplines, types of institutions, and geographic locations. Analyses indicated clear congruence between quantitative and qualitative data. Definitions of DT aligned with well-known models of DT. Motivations for teaching DT included the promotion of personal development, DT proficiency, impact, and interpersonal skill development. Other positive student outcomes observed included increases in enthusiasm, self-awareness, empowerment, optimism, and a sense of belonging. Negative student outcomes included time constraints, teamwork conflicts, and student frustration. Conclusion: Faculty believe that DT leads to highly valuable social innovation skill sets for students. This cross-institutional, multi-disciplinary study provides critical insight into faculty experiences and motivations for teaching DT, offering various strategies for instructors and institutions interested in fostering the uptake of DT within higher education.